Inhibiting effects of 1-butyl-3-methyl imidazole tetrafluoroborate on coal spontaneous combustion under different oxygen concentrations. (1st November 2019) - Lü, Hui-Fei; Xiao, Yang; Deng, Jun; Li, Da-jiang; Yin, Lan; Shu, Chi-Min
Abstract: Exothermicity is a key parameter for evaluating coal spontaneous combustion (CSC). A suitable oxygen concentration is essential for CSC. Ionic liquids (ILs), which are a popular type of fire prevention material, inhibit coal oxidation. 1-Butyl-3-methyl imidazole tetrafluoroborate ([BMIM][BF4 ]) was used at various mass ratios (0, 2, 5, and 10 mass%) to treat coal to inhibit CSC. Through simultaneous thermal analysis tests, coal samples were investigated in atmospheres with oxygen concentrations of 5, 10, 15, and 21 vol%. The results indicated that the mass loss decreased with increasing IL content. However, the mass loss did not decrease indefinitely with increasing IL content. The lowest mass loss was observed at an IL concentration of approximately 7.5 mass%. The inhibition increased with decreasing oxygen concentrations. Moreover, the inhibiting effect first increased slowly until the IL concentration exceeded 10 mass%, after which the inhibiting effect increased rapidly. The relationship between the exothermic rate and the mass loss rate of the coal at Stage 2 of the reaction was comparatively analysed. The reaction rate between oxygen and coal was the key factor influencing the exothermic rate. In the oxidation of coal, both the oxygen concentration and inhibitor content affected the comprehensive combustion index of coal. Highlights: The relationship between the amount of IL added and the mass loss/CAIT was defined. Fitted curves of the mass loss ( y 3 ) and oxygen concentration ( x 2 ) were obtained. A high mass loss or heat accumulation led to an easy occurrence of CSC. Comprehensive index parameters under different conditions were explored and elucidated.